PERBEDAAN HASIL BELAJAR FISIKA MELALUI METODE PEMBELAJARAN JIGSAW DAN THINK PAIR SHARE (TPS) PADA SISWA KELAS X MAN 15 JAKARTA - Intan Irawati (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The aim of research was to measure the differences of students’ physics achievement which taught by jigsaw type and think pair share (TPS) type on electro dynamic topic. The research conducted at tenth grade-1,-2 and -3 (X1, X2 and X3) in State Islamic Senior High School (MAN) 15 Jakarta. The research was experiment method. Jigsaw method was applied in X-1, TPS method was applied in X2 and classical method was applied in X3. Physics achievement test was used as research instrument. Data analysis used ANOVA technique to test the differences of experimental groups. Result of Fmeasure (4,210) > F table (2; 100; 0.05) was 3.10 and sig (0.018) < α, so that we refused H0. Table post hoc test showed the mean differences were sygnifican in classical method class and TPS method class. Both groups classical and TPS class have differences mean score. Experiment result suggested physics teacher to apply TPS method in teaching learning. This method proved can increase the physics score test more effective than jigsaw method. Keywords: achievement, jigsaw method, learning, physics, Think Pair Share (TPS) method.